2020
DOI: 10.1371/journal.pone.0238256
|View full text |Cite
|
Sign up to set email alerts
|

Two Doublesex1 mutants revealed a tunable gene network underlying intersexuality in Daphnia magna

Abstract: In recent years, the binary definition of sex is being challenged by repetitive reports about individuals with ambiguous sexual identity from various animal groups. This has created an urge to decode the molecular mechanism underlying sexual development. However, sexual ambiguities are extremely uncommon in nature, limiting their experimental value. Here, we report the establishment of a genetically modified clone of Daphnia magna from which intersex daphniids can be readily generated. By mutating the conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…However, due to stochasticity in gene expression [ 11 , 12 ], there would be the noise in gene expression. In a previous study, we proved that improper expression of Dsx1 changes the expression profile of its downstream genes resulting in intersex [ 13 ]; which suggested that the stochastic transcription of Dsx1 causing population heterogeneity, should be avoided. In the presence of the Shep, the Dsx1 mRNA from the transcriptional noise cannot be translated immediately because of the binding of the Shep at the TGE-like motif.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to stochasticity in gene expression [ 11 , 12 ], there would be the noise in gene expression. In a previous study, we proved that improper expression of Dsx1 changes the expression profile of its downstream genes resulting in intersex [ 13 ]; which suggested that the stochastic transcription of Dsx1 causing population heterogeneity, should be avoided. In the presence of the Shep, the Dsx1 mRNA from the transcriptional noise cannot be translated immediately because of the binding of the Shep at the TGE-like motif.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotyping of the Dsx1 mutants Line A and Line B aforementioned also showed Dsx1 dependency of male trait development ( Figure 4 ) ( Nong et al, 2017 ; Nong et al, 2020 ). Compared to Line B males, Line A males showed more severe feminization throughout development, which were obvious in the first antennae and carapace ( Figure 9A ).…”
Section: Introductionmentioning
confidence: 88%
“…Both lines have a single copy of the mCherry reporter on one of the Dsx1 alleles. In Line A, another Dsx1 allele is mutated with a 6-bp deletion at the start codon, which suggests that this line does not produce any intact Dsx1 protein ( Nong et al, 2020 ). In contrast, Line B has a wild-type Dsx1 gene on another allele.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations